Assessment and analysis of the global ionosphere maps over China based on CMONOC GNSS data - Zhu, Fuying; Yang, Jian; Qing, Yun; Li, Xinxing (Frontiers in Earth Science, 2023)
The global ionosphere map (GIM) total electron content (TEC) data are extensively employed as to statistically study the seismic ionospheric disturbance characteristics. Due to the limitation of spatial coverage of ground based GNSS receivers, in many regions, the GIM TEC results are obtained by interpolation or extrapolation, and therefore the actual accuracy is different. In this paper, based on the CMONOC GNSS data, a high precision regional ionospheric map (RIM) model over China is established, and the assessment and analysis of the post-processed IGS GIM over China are conducted. Statistical results show that the average RMS of IGS GIM over China is less than 2 TECu. The comparison of the TEC values calculated by the GIM with the RIM shows that the two models give similar results. The Bias and STD of the difference over most of China is less than 2 TECu except some low latitude area. Meanwhile, the correlation between GIM and RIM is better in daytime than at night, and it is not affected by space electromagnetic disturbance. The assessment results of accuracy in this paper are only applicable to China region, and the accuracy of other regions needs to be further assessed.